On Efficient Estimation in Successive Sampling Over Two Occasions - Kumar Tiwari , Kuldeep; Bhougal, Sandeep; Kumar, Sunil (Thailand Statistician, 2023)
Surveys often get repeated on many occasions over years or seasons to study the change in the characteristics over the period. Using the data from the previous occasion also improves the estimation on the current occasion. We have worked on the problem of estimating the population mean in successive sampling over two occasions. To increase the efficiency in the estimation of the population mean on the current (second) occasion in two occasion successive sampling, we have proposed an estimator t by using the convex linear combination of the estimators based on units, which is drawn afresh at the current occasion and based on units, which are retained from the previous occasion. The expressions of bias and mean square error for the proposed estimator are calculated and optimal replacement policy is also discussed for the said case. To show the validity of the work, we made an empirical study followed by an application to a case study.